Inhibition of diverse opportunistic viruses by structurally optimized retrograde trafficking inhibitors. Issue 9 (1st May 2019) - Desai, Dhimant; Lauver, Matthew; Ostman, Alexandria; Cruz, Linda; Ferguson, Kevin; Jin, Ge; Roper, Brianne; Brosius, Daniel; Lukacher, Aron; Amin, Shantu; Buchkovich, Nick
Graphical abstract: Abstract: Opportunistic viruses are a major problem for immunosuppressed individuals, particularly following organ or stem cell transplantation. Current treatments are non-existent or suffer from problems such as high toxicity or development of resistant strains. We previously published that a trafficking inhibitor that targets a host protein greatly reduces the replication of human cytomegalovirus. This inhibitor was also shown to be moderately effective against polyomaviruses, another family of opportunistic viruses. We have developed a panel of analogues for this inhibitor and have shown that these analogues maintain their high efficacy against HCMV, while substantially lowering the concentration required to inhibit polyomavirus replication. By targeting a host protein these compounds are able to inhibit the replication of two very different viruses. These observations open up the possibility of pan-viral inhibitors for immunosuppressed individuals that are effective against multiple, diverse opportunistic viruses.